At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure! Let's solve the given system of linear equations using the substitution method step-by-step.
### Part i:
Solve the following system of equations using the substitution method:
[tex]\[ \begin{cases} 3x - 2y = 5 \\ 2x + y = 8 \end{cases} \][/tex]
1. Solve the second equation for [tex]\( y \)[/tex]:
[tex]\[ 2x + y = 8 \quad \Rightarrow \quad y = 8 - 2x \][/tex]
2. Substitute [tex]\( y = 8 - 2x \)[/tex] into the first equation:
[tex]\[ 3x - 2(8 - 2x) = 5 \][/tex]
Simplify the equation:
[tex]\[ 3x - 16 + 4x = 5 \quad \Rightarrow \quad 7x - 16 = 5 \quad \Rightarrow \quad 7x = 21 \quad \Rightarrow \quad x = 3 \][/tex]
3. Substitute [tex]\( x = 3 \)[/tex] back into the equation [tex]\( y = 8 - 2x \)[/tex] to find [tex]\( y \)[/tex]:
[tex]\[ y = 8 - 2(3) \quad \Rightarrow \quad y = 8 - 6 \quad \Rightarrow \quad y = 2 \][/tex]
Therefore, the solution to the first system of equations is:
[tex]\[ (x, y) = (3, 2) \][/tex]
### Part ii:
Solve the following system of equations using the substitution method:
[tex]\[ \begin{cases} 7x - y = 14 \\ 8x - 2y = 16 \end{cases} \][/tex]
1. Solve the second equation for [tex]\( y \)[/tex]:
[tex]\[ 8x - 2y = 16 \quad \Rightarrow \quad -2y = 16 - 8x \quad \Rightarrow \quad y = \frac{8x - 16}{2} \quad \Rightarrow \quad y = 4x - 8 \][/tex]
2. Substitute [tex]\( y = 4x - 8 \)[/tex] into the first equation:
[tex]\[ 7x - (4x - 8) = 14 \][/tex]
Simplify the equation:
[tex]\[ 7x - 4x + 8 = 14 \quad \Rightarrow \quad 3x + 8 = 14 \quad \Rightarrow \quad 3x = 6 \quad \Rightarrow \quad x = 2 \][/tex]
3. Substitute [tex]\( x = 2 \)[/tex] back into the equation [tex]\( y = 4x - 8 \)[/tex] to find [tex]\( y \)[/tex]:
[tex]\[ y = 4(2) - 8 \quad \Rightarrow \quad y = 8 - 8 \quad \Rightarrow \quad y = 0 \][/tex]
Therefore, the solution to the second system of equations is:
[tex]\[ (x, y) = (2, 0) \][/tex]
### Summary of Solutions:
- For the first system: [tex]\((x, y) = (3, 2)\)[/tex]
- For the second system: [tex]\((x, y) = (2, 0)\)[/tex]
These solutions are found by following the step-by-step substitution method.
### Part i:
Solve the following system of equations using the substitution method:
[tex]\[ \begin{cases} 3x - 2y = 5 \\ 2x + y = 8 \end{cases} \][/tex]
1. Solve the second equation for [tex]\( y \)[/tex]:
[tex]\[ 2x + y = 8 \quad \Rightarrow \quad y = 8 - 2x \][/tex]
2. Substitute [tex]\( y = 8 - 2x \)[/tex] into the first equation:
[tex]\[ 3x - 2(8 - 2x) = 5 \][/tex]
Simplify the equation:
[tex]\[ 3x - 16 + 4x = 5 \quad \Rightarrow \quad 7x - 16 = 5 \quad \Rightarrow \quad 7x = 21 \quad \Rightarrow \quad x = 3 \][/tex]
3. Substitute [tex]\( x = 3 \)[/tex] back into the equation [tex]\( y = 8 - 2x \)[/tex] to find [tex]\( y \)[/tex]:
[tex]\[ y = 8 - 2(3) \quad \Rightarrow \quad y = 8 - 6 \quad \Rightarrow \quad y = 2 \][/tex]
Therefore, the solution to the first system of equations is:
[tex]\[ (x, y) = (3, 2) \][/tex]
### Part ii:
Solve the following system of equations using the substitution method:
[tex]\[ \begin{cases} 7x - y = 14 \\ 8x - 2y = 16 \end{cases} \][/tex]
1. Solve the second equation for [tex]\( y \)[/tex]:
[tex]\[ 8x - 2y = 16 \quad \Rightarrow \quad -2y = 16 - 8x \quad \Rightarrow \quad y = \frac{8x - 16}{2} \quad \Rightarrow \quad y = 4x - 8 \][/tex]
2. Substitute [tex]\( y = 4x - 8 \)[/tex] into the first equation:
[tex]\[ 7x - (4x - 8) = 14 \][/tex]
Simplify the equation:
[tex]\[ 7x - 4x + 8 = 14 \quad \Rightarrow \quad 3x + 8 = 14 \quad \Rightarrow \quad 3x = 6 \quad \Rightarrow \quad x = 2 \][/tex]
3. Substitute [tex]\( x = 2 \)[/tex] back into the equation [tex]\( y = 4x - 8 \)[/tex] to find [tex]\( y \)[/tex]:
[tex]\[ y = 4(2) - 8 \quad \Rightarrow \quad y = 8 - 8 \quad \Rightarrow \quad y = 0 \][/tex]
Therefore, the solution to the second system of equations is:
[tex]\[ (x, y) = (2, 0) \][/tex]
### Summary of Solutions:
- For the first system: [tex]\((x, y) = (3, 2)\)[/tex]
- For the second system: [tex]\((x, y) = (2, 0)\)[/tex]
These solutions are found by following the step-by-step substitution method.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.